Comparative analysis of profitability among different cultivars of chrysanthemum flowers using HDPE and tarpaulin as covering materials - Ali, Haidar Shah; Priyanka, Thakur; Pardeep, Kumar; Anju, Sharma; Pandey, R K; Rakesh, Kumar; Nitesh, Kaushal; Padi, Mahesh (Plant Science Today, 2026)
Chrysanthemums are popular worldwide due to their beautiful range of colors, shapes and flower sizes. Since they are in high demand during the off seasons, the present investigation was carried out on the effect of covering materials on off-season flower production of chrysanthemums during 2022–23. The covering materials used in the experiment included tarpaulin and three cultivars, each of standard and spray type. In the present investigation, the profitability of six chrysanthemum flower cultivars, i.e., White Star, Yellow Star, Purnima, Surf, Apricot Parasol and Wellspring White were assessed under two types of covering materials i.e. High-Density Polyethylene (HDPE) and tarpaulin. The results showed that Yellow Star (2.08), with HDPE as a covering material performed best with respect to return on investment, followed by Surf (2.01). In contrast, the cultivar Wellspring White has the lowest benefit-cost ratio (BCR) of 1.38. The cultivar White Star (1.92) and Apricot Parasol (1.65) have moderate BCRs. The results further showed that the cultivar Yellow Star has the highest BCR value among others when HDPE is used as a covering material. The study also presents the yield and profitability of these cultivars under tarpaulin covering. Yellow Star (2.65) has a maximum BCR, followed by white Star (2.26) which was almost twice that of Purnima (1.89). Surf and Apricot Parasol also have typical BCRs (1.17 and 1.09, respectively), while Wellspring White has a minimum BCR of 1.04. Finally, the study revealed that Yellow Star is the most beneficial variety in terms of yield and return under both HDPE and tarpaulin, followed by White Star and Purnima. These results provide valuable insights for both cut flower farms and investors, highlighting the significance of cultivar choice and covering material type when making investment or resource allocation decisions.